Orai1 contributes to the establishment of an apoptosis-resistant phenotype in prostate cancer cells - Flourakis, M; Lehen'kyi, V; Beck, B; Raphaël, M; Vandenberghe, M; Abeele, F V; Roudbaraki, M; Lepage, G; Mauroy, B; Romanin, C; Shuba, Y; Skryma, R; et al. (Cell death & disease, 2010)
The molecular nature of calcium (Ca 2+ )-dependent mechanisms and the ion channels having a major role in the apoptosis of cancer cells remain a subject of debate. Here, we show that the recently identified Orai1 protein represents the major molecular component of endogenous store-operated Ca 2+ entry (SOCE) in human prostate cancer (PCa) cells, and constitutes the principal source of Ca 2+ influx used by the cell to trigger apoptosis. The downregulation of Orai1, and consequently SOCE, protects the cells from diverse apoptosis-inducing pathways, such as those induced by thapsigargin (Tg), tumor necrosis factor α , and cisplatin/oxaliplatin. The transfection of functional Orai1 mutants, such as R91W, a selectivity mutant, and L273S, a coiled-coil mutant, into the cells significantly decreased both SOCE and the rate of Tg-induced apoptosis. This suggests that the functional coupling of STIM1 to Orai1, as well as Orai1 Ca 2+ -selectivity as a channel, is required for its pro-apoptotic effects. We have also shown that the apoptosis resistance of androgen-independent PCa cells is associated with the downregulation of Orai1 expression as well as SOCE. Orai1 rescue, following Orai1 transfection of steroid-deprived cells, re-established the store-operated channel current and restored the normal rate of apoptosis. Thus, Orai1 has a pivotal role in the triggering of apoptosis, irrespective of apoptosis-inducing stimuli, and in the establishment of an apoptosis-resistant phenotype in PCa cells.